Impact of the Union Budget on the Indian Stock Market - Pandya, Ishan Harendrakumar (Indian Journal of Finance, 2014)
The stock market of a country is said to act as a barometer of its economic health. All economic activities happening in the country and outside the country lead to a change in the market conditions. Different market players who invest their money in stocks are not only interested to know about the rise and fall in the stock market, they are keen to know about the various economic events / activities that are going to take place in the near future. The stock market reacts depending on how the investors interpret the economic activities. The Union Budget is perhaps the most watched event in economic policy making in India. The core fiscal issues - taxation, expenditures, and the fiscal deficit - are obviously important for macroeconomics. In addition, governments have often chosen to use the Budget speech as a mechanism for announcing important new policy initiatives, and for outlining some plans for economic policy in the coming months. The stock market response to a Budget is often viewed as an important summary statistic of the ’quality’ of a Budget in terms of improving the macroeconomic prospects. In this research paper, I intended to find an interplay between the Budget and the stock market, in the areas like informational efficiency and implications for portfolios and trading. In this study, the main focus is on return and volatility impact along with different event windows.